SIMPLIFYING SHARF MATERIALS (EXPERIMENTAL STUDY AT AT-TAQWA ISLAMIC BOARDING SCHOOL, SUKABUMI, WEST JAVA) / ØªØ¨Ø³ÙŠØ· Ø§Ù„Ù€Ù…ÙˆØ§Ø¯ Ø§Ù„ØµØ±ÙÙŠØ© (Ø¯Ø±Ø§Ø³Ø© ØªÙ€Ø¬Ø±ÙŠØ¨ÙŠØ© ÙÙŠ Ù…Ø¹Ù‡Ø¯ Ø§Ù„ØªÙ‚ÙˆÙ‰ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠ Ø³ÙˆÙƒØ§Ø¨ÙˆÙ…ÙŠ Ø¬Ø§ÙˆÙ‰ Ø§Ù„ØºØ±Ø¨ÙŠØ©) - Istiya Rahayu Dwi Parwati (IAIN Batusangkar, Indonesia, 2021)
This study aims to reveal the need for simplification of Sharf materials for Arabic language learners, what can be simplified, and to test the effectiveness of using simple Sharf materials on the success of Sharf learning. This research used mixed method by combining qualitative and quantitative method to collect the data in order to produce more comprehensive facts and researcher had a freedom to use all data collection tools to get all required data. The findings explained that the simplification of Sharf materials is an effort to facilitate the learning of Arabic language, so that the process of teaching and learning Sharf is easier and could be done in a relatively short time. The materials simplification focused on simplifying classical wazn sharf by only presenting functional wazn-wazn which is widely used in Arabic, namely 31 chapters of wazn fi’il is simplified into 14 chapters, as well as simplifying binyah kalimat from 11 patterns to 5 patterns. The simplification is present as a solution to the difficulty of learning sharf. The result of pretest and posttest showed a significant difference between the experimental and control class, as the result of the gain test, 0.35 for experimental class and 0.14 for control class, which means that the effectiveness level of experimental class is higher than control class.